2014
DOI: 10.9790/1684-11655662
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi Based Mechanical Property Optimization Of As Weld Al-65032 Alloy Using Tig Welding

Abstract: In recent days, light materials like aluminum alloys are becoming more prominent in real world.In this paper, the parametric design of aluminum alloy (AL 65032) is carried out for the optimum mechanical properties (UTS, 0.2% proof stress, percentage elongation) using Taguchi techniques. This paper considered only for weld conditions. Hence the parametric design is carried out for TIG welding with as weld condition and with control parameters gas pressure, current, groove angle and preheat. Three levels are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Research showed that an optimal welding speed could produce a joint with high mechanical strength, excellent microstructure, and good morphology [5]. Eshwar Materials 2023, 16, 3732 2 of 22 et al (2014) found that the input parameter has a substantial role in determining the weld quality, which primarily includes bead width and height, and penetrating the area, thermal, and residual stresses, resulting in minimizing the life of a weld joint [6]. Researchers have tried to work on different welding processes regarding weld bead geometry, temperature, and stress fields.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that an optimal welding speed could produce a joint with high mechanical strength, excellent microstructure, and good morphology [5]. Eshwar Materials 2023, 16, 3732 2 of 22 et al (2014) found that the input parameter has a substantial role in determining the weld quality, which primarily includes bead width and height, and penetrating the area, thermal, and residual stresses, resulting in minimizing the life of a weld joint [6]. Researchers have tried to work on different welding processes regarding weld bead geometry, temperature, and stress fields.…”
Section: Introductionmentioning
confidence: 99%